Design and evaluation of performance metrics of a pentaband broadband microstrip patch antenna for mm wave applications - Jana, Subhasis; Kumar Singh, Raj; Mamta, Kumari (Institute of Advanced Engineering and Science, 2025)
This paper reports design and results of a microstrip patch antenna for broadband application in the millimeter wave communication with multiband features. Electromagnetic solver high-frequency structure simulator (HFSS) is employed to measure the effectiveness of the electromagnetic properties and electrical behaviour of the antenna. The proposed microstrip patch antenna (MPA) can be easily fabricated on a single substrate using standard photolithography process to attach the radiating element and feed lines to the dielectric material. On a 4.93 mm×5.86 mm metallic patch, over FR4 epoxy substrate with dielectric constant 4.4 and loss tangent 0.03, two L-shaped slots are placed along with a few micro slots of varied dimensions, and the antenna is fed with microstrip feedline with resistive load termination of 50 Ω. Pentaband resonant frequencies are realized in the K-band at 13.6 GHz, 23.2 GHz, 29.68 GHz, 32.96 GHz, and 38.56 GHz, with minimum return loss of -23.17 dB, bandwidth 2.32 GHz, omnidirectional radiation pattern, and maximum reported gain of 4.5 dB. The designed antenna achieved good electromagnetic radiation properties and electrical behaviour, and is a good choice for broadcasting over short distances, surveillance and monitoring, wireless sensor backhauls and telecommunication in the K-band networks.